An investigation of compounds occurring in leonotis species - Naidu, Krishna (Rhodes University, Faculty of Pharmacy, Pharmacy, 1970)
Two labdane diterpenoids 8-hydroxymarrubiin and leonitin were isolated from Leonotis dysophylla (Benth.) and Leonotis leonitis respectively. Spectral studies of 8-hydroxymarrubiin, Câ‚‚â‚€Hâ‚‚â‚ˆ Oâ‚…Ê» showed the presence of a Î² -substituted furan, a Ïª-lactone, three tertiary methyl groups and tertiary hydroxyl group (s). The NMR spectrum of 8-hydroxymarrubiin and marrubiin Câ‚‚â‚€Hâ‚‚â‚ˆOâ‚„Ê» were almost identical with the exception of the Câ‚ â‚‡- methyl group which appeared as a singlet in 8-hydroxymarrubiin and as a doublet in marrubiin. The extra oxygen atom was therefore assumed to be present as a hydroxyl group substituted in the Câ‚ˆâ‚‹ position. This was further confirmed by the formation of an epoxide and a ÏªÏŒ-dilactone. Leonitin, Câ‚‚â‚€Hâ‚‚â‚ˆOâ‚‡Ê» was shown by spectral and chemical evidence to be a diterpenoid dilactone possessing an ester function and an ether linkage. Comparison of the NMR spectra of compound X and leonitin suggested that the acetoxy function occurs in the Câ‚‚â‚€- position. This was further supported by the formation of a 'ÏªÏŒ -dilactone. The absence of a Î² -furan moiety was apparent from chemical and spectral evidence, A structure for leonitin is proposed and aspects of its stereochemistry discussed.
Keywords: Leonotis -- Analysis; Chemistry -- Analytic; Nuclear magnetic resonance